Audouin Dollfus, astronome du XX$^{\protect e}$ siècle - Chanetz, Bruno; Broc, Alain; Jung, Philippe (Comptes Rendus. Mécanique, 2023)
Canadian astrophysicist Hubert Reeves (April 2011) considers Audouin Dollfus to be one of the greatest contemporary French astronomers. In particular, he discovered Saturn’s satellite Janus, determined the composition of the soil on Mars, detected atmospheric residue on Mercury and helped choose the landing site for the Apollo 11 mission, which enabled Neil Armstrong to set foot on the Moon for the first time. He was also a high-flying aeronaut, as he still holds the world record for the highest manned flight in a balloon equipped with an astronomical telescope.